Detecting Southern California’s White Sharks With Environmental DNA - Lafferty, Kevin D.; Benesh, Kasey C.; Mahon, Andrew R.; Jerde, Christopher L.; Lowe, Christopher G. (Frontiers in Marine Science, 2018)
To improve ability to detect white sharks without the need for tags, or visual census, we developed a species-specific environmental DNA (eDNA) assay that targets a 163 bp fragment of the white shark (Carcharodon carcharias) mitochondrial cytochrome B gene on a digital droplet PCR (ddPCR) platform. We used this marker to detect white shark DNA in 250 ml water samples taken from across two sites in Santa Barbara, California (USA) frequented by juvenile white sharks. We did not detect white shark DNA in samples from two neighboring sites where sharks are presumably absent, suggesting that eDNA can indicate nearby white sharks. This marker development, testing, and opportunistic application in a region with known distributions of white sharks indicates that environmental DNA could be developed further to monitor white sharks, thereby informing conservation planning and public safety. With the potential increase in white shark populations due to decades of protection, there is a need for fishery independent methods for assessing white shark distributions, and eDNA may provide be an ideal, non-intrusive tool for coastal assessments.